The suitability of Boran and its crosses with European breeds for beef production under range conditions in Kenya - Tonn, R. (1974)
1.Including their production in the subsistence sector, the 9.1 million cattle comprise 88% of the gross production value of the live stock sector of Kenya. Approximately 4/5 of the land area, consisting of natural steppes and savannahs in semi-arid to arid climatic zones, can be most economically used through extensive beef cattle production. The stock consists of the small East African Shorthorn zebu, predominant in the humid zones, and the large Shorthorn zebu, predominant in the arid regions of Norther Kenya, from which the “improved” boran cattle were developed through selection.2. This investigation analyses the production characteristics of the Boran cattle and its crosses with European breeds in relation to the ecological potential of the various ranches in the semi-arid to arid climatic zones. 3. The data stem from five private ranches in the rift valley province of Kenya; their ecological potential is largely determined by the amount and distribution of precipitation. The stock consisted mainly of Boran cattle, supplemented by crosses with Friesian, Ayrshire, Charolais, Aberdeen Angus, Simmental, Hereford, and Santa Gertrudis. 4. The data are composed of the following complexes of characteristics and numbers of animals: a)Weight development of bulling heifers until joining age. –2403 weaning weights and weights after weaning at an age between 300 and 999 days; b) rearing production and weights of cows 890 birth weights, 8506 weaning weights, 5631 cow weights; c) fattening performance and carcass quality of range-fed steers (n=348) weaning weights, live weights before slaughter, age at slaughter, carcass weights, carcass yield, size of eye muscle area, marbling of eye muscle, carcass composition. 5. The data were statistically processed according to the least-squares method of Harvey (1960) on a weights were conducted separately, by ranch, because of the different ecological conditions. 6. The following influences were investigated in the analysis: a) weight development of bulling heifers until joining age – ranches, years, birth month, age of dam, production purpose, and dam’s stage of pregnancy, and age of animal; b) rearing performance and weights of cows – years, birth periods, sex of calf, sire’s and dam’s breed, age and weight of dam, length of calving interval, age of dam at first calving, and weaning age; c) fattening performance and carcass quality – ranch, date of slaughter breeds, carcass grades. 7. the weight development of Boran bulling heifers until first joining is characterized by a negative relationship between weaning weight gain after weaning. Lighter calves gain more weight after weaning than heavier calves. This compensatory growth is caused mainly by different qualities of material environments during the suckling period and has a leveling effect on the weight development after weaning. 8. The birth weights of the calves from Ranch 1 are significantly influenced by birth season, sex, and sire’s and dam’s breed, whereas the influences of yeas, age of dam, and length of preceding calving interval remain insignificant. The heritability estimated for 703 birth weights of calves from 16 progenies amounts to 0.44±0.169. 9. The amount and direction of the influencing factors on the weaning weights analyzed according to ranch show, in part, a clear dependence on the ecological potential. On all ranches, the weaning weights are strongly influenced by years and birth periods. Precipitation and its temporal distribution with its effect on fodder growth forms, besides changes in management and outbreaks of diseases, the basis of these influence factors. 10. The sex of the calf, the birth weight, the length of the calving intervals, the age of the dam at its last calving, and the weaning age of the calf vary from ranch to ranch in their influences on weaning weights. 11. The influencing of weaning weights through the cow weights in investigated with different methods: a) with uncorrected cow weights, b) With cow weights corrected for the cow’s age and stage of pregnancy, c)with cow weights within age classes of cows. 12. with the exception of Ranch 1, which had the lowest ecological potential, the weaning weights of the calves are positively correlated (0.16 to 0.31) with the cow weights. In Ranch 2, which had a relatively high ecological potential, the weaning weights increased linearly with the cow weights; the relationship in Ranches 3 and 4 was linear-quadratic. An increase of 100 kg in cow weight produced an increase of 9.0 to 14.6 kg in weaning weight. The correction of cow weights for the age and stage of pregnancy of the cow did not significantly alter the relationship to weaning weight. 13. Within the different age classes, the 5.0 to 7.9 year old cows show the closest positive relationship between their weights and the weaning weights of their offspring. The 3.0 to 4.9-year-old cows do not show a significant relationship, whereas the weaning weights of calves from cows over 8 years increase only until a cow weight of 390 kg, and then decrease. 14.The cow weights are negatively correlated with the characteristic, weaning weight per kg cow weight. Lighter cows produce more weaning weight per kg body weight than heavier cows. 15. The offspring from crosses of Friesian, charolais, Simmental with Boran weigh 8 to 25% more at weaning than the Boran calves. The weight superiority of the Hereford, Aberdeen Angus-, and Santa Gertrudis crosses over the Boran calves amounts to 3 to 9%. 16. The cows of the F1-Generation from the cross with Friesian and Santa Gertrudis produce calves, which are 24 to 28% heavier than those from the Boran cows. This superiority disappears when the crossbred cows are kept in the Dairy Ranching system. 17. The heritabilities of 0.28 to 0.30, estimated for 2601 weaning weights of Boran calves from 53 pro genies, are within the range of those given in the literature on other beef breeds. 18. Besides years and calving season, the age of the dam and the stage of pregnancy have the greatest influence on the weights of the beef cows at weaning time of their calves. Te F1-cross-bred cows weigh 7 to 26%, the cows from three-bred crosses 15 to 23 %, the back crosses to Boran 4 to 15 %, and cows from back crossing to the European breeds 20 to 26 % more than the pure-bred Boran cows. 19. The range-fed steers from crossing between Friesian and Boran are about 3 months younger and 8 to 15% heavier at slaughter than the Boran Steers. 20. The carcass yield, the marbling of the eye muscle, and the size of the eye muscle area reflect the ecological potential of the home ranches of the steers. Aberdeen Angus crosses from the Ranch 2 with a higher range potential have the highest yield, 57.4 %, and the Friesian crosses from ranch 1 have with 53.9 & the lowest crcass yield. 21. The carcass composition is estimated from the specific gravity of the joint of the 10th rib. The carcasses of steers from the ranch with a low ecological potential condition less fat, but more muscle and bone tissue than those from the other ranches. 22. Carcass grade, carcass yield, and marbling score of eye muscle are positively correlated with the relative proportion of fat, and negatively with the size of the eye muscle area and the relative proportions of muscle and bone tissue. 23. The rearing performance of cows with different body weights are compared in a simplified model calculation, taking into consideration the energetic maintenance and production requirements. Assuming equal fertility, the lighter cows produce more weaning weight from a certain amount of nutrients, but less cow weight in form of cull cows than heavier cows. The greater growth potential of their offspring in creases the competitive value of the heavier cows. 24. The desirable size of beef cow in range cattle production in Kenya depends on the ecological potential of the location. The heavier cows are sufficient for the higher growth potential of their offspring. The advantage of the lighter cows with lower maintenance requirements increases in locations with low ecological potential, particularly when the low by crossing them with European breeds, and sell and fatten these x-bred animals in locations with high ecological potential. 25. Besides the extension and intensification of crossbreeding with European dual-purpose and beef breeds, Kenyan beef production could be increased through improvements in the breeding of Boran cattle on the large ranches in those locations with low to average potential by means of beef recording program. Selection criteria and possibilities for the estimation of the breeding values of bulling heifers, cows, and bulls, are discussed in this investigation. 26. The various ecological zones of Kenya’s range areas demand an optimal adaptation of the cattle’s genotype to the local range potential. Through a separation of breeding and fattening operations in a stratification between ranches with different ecological potentials, beef production will reach new heights.